Analyzing the Elements of Effective Professional Development in Teacher Education (THE ACADEMIA, 2025)
The purpose of this study is to identify the components of effective professional development in teacher education. Information is analyzed in a descriptive way in this study. A systematic review of papers published in the teaching, teacher professional and teacher education journal identifies key components that contribute to successful teacher education. Teacher education is important dimension for promoting effective professional growth. Effective professional development is identified as crucial for educators to develop the necessary pedagogical skills for teaching field. The elements of teacher education include collaboration, learning experiences, cooperation, deliberation, active learning, modeling; coaching, mentorship and support mechanisms, feedback and reflection, continuous involvement, and a focus on student outcomes are found. These factors enhance instructional effectiveness and ultimately resulting in continued improvements in the quality of teaching. Effective professional development should be regular, context-sensitive, and focus toward improving teaching techniques. Similarly, integrating the use of technology and new teaching practices is very important in contemporary teacher education. Teacher education programs are evaluated and adapted on a continuous basis to meet the changing demands of teachers. The findings indicate that recent trends in professional development for teachers emphasize enhancing teaching skills, classroom management, and subject matter knowledge. The approach to teacher education should be collaborative and collegial learning environment. The future researchers should do research on culturally responsive teaching in teacher education and the effect of understood bias training on teacher attitudes and practices.